Valorization of Food Waste Leachates through Anaerobic Digestion - Ioannis Kontodimos; Chrysovalantis Ketikidis; Panagiotis Grammelis (Engineering Proceedings, 2022)
According to the European Union data, on average 173 kg per person of total food waste (organic waste) is produced annually, of which 92 kg per person comes from households (organic waste). Food waste is defined as the waste from households, restaurants, canteens, and food industries, as well as markets. The importance of food waste stretches from the environmental pressures to the economic and social impacts. An environmental technology for the biodegradation of food waste is anaerobic digestion. It is a very attractive technique and combines waste treatment and renewable energy recovery. This study investigates the characteristics of food waste leachates from composting buckets and their valorization as a substrate for the anaerobic digestion process. A complete characterization of different food waste leachates was conducted (pH, COD, VFAs, heavy metals, etc.). The food waste leachates proved to be an ideal feedstock for anaerobic digestion. In this direction, batch tests were performed to evaluate the methane yield of the food waste leachates under different operating conditions. Three different SIR ratios were tested (0.5, 1.0, and 1.5). An SIR equal to 0.5 proved to be the best as the higher methane yield was achieved. The removal of the COD under all the operating conditions was higher than 70%, with the higher removal (85.18%) for an SIR equal to 1.5.